Peningkatan Perekonomian Masyarakat dalam Perspektif Al-Qur’an (Study Kreativitas Kerajinan Pelepah Pisang Sebagai Upaya Meningkatkan Perekonomian Masyarakat Desa Trepan Babat Lamongan) - Nurus safa'atillah; Ummi Rokhmatillah; Hidayatur Rohmah; Merisa Anggraeni (Universitas Batanghari, 2022)
Trepan Village has natural potential that is very useful in improving its economic welfare, namely there are banana trees that grow in this Trepan Village area. The surrounding community takes advantage of the natural potential that already exists, namely the use of banana stems into various beautiful crafts where this craft can increase the economy and increase the income of the community itself. This study aims to determine whether the creativity of the banana midrib craft can improve the economic welfare of the Trepan village community. The author uses a qualitative descriptive approach, namely by conducting interviews, observations, documentation as data collectors. The results showed that the use of banana midrib into handicrafts had a great impact on the economic welfare of the people of Trepan village. Through the creative economy, it was found that they were able to reduce the unemployment rate slightly and bring change to society, they were able to meet the needs of their families and the family's economic situation from better craftsmen. It was also found that by using the banana midrib, the community got additional income to meet the family economy, which income could increase the welfare of the people of Trepan Village.